Cooperative transport tasks with robots using adaptive non-conventional sliding mode control. (September 2018) - Gracia, Luis; Solanes, J. Ernesto; Muñoz-Benavent, Pau; Esparza, Alicia; Valls Miro, Jaime; Tornero, Josep
Abstract: This work presents a hybrid position/force control of robots aimed at handling applications using multi-task and sliding mode ideas. The proposed robot control is based on a novel adaptive non-conventional sliding mode control used to robustly satisfy a set of inequality constraints defined to accomplish the cooperative transport task. In particular, these constraints are used to guarantee the reference parameters imposed by the task (e.g., keeping the load at a desired orientation) and to guide the robot using the human operator's forces detected by a force sensor located at the robot tool. Another feature of the proposal is the multi-layered nature of the strategy, where a set of four tasks are defined with different priorities. The effectiveness of the proposed adaptive non-conventional sliding mode control is illustrated by simulation results. Furthermore, the applicability and feasibility of the proposed robot control for transport tasks are substantiated by experimental results using a redundant 7R manipulator. Highlights: We develop a robot control for cooperative transport tasks. The controller is based on an adaptive non-conventional sliding mode control. We use a multi-layered strategy based on four tasks with different priorities. The effectiveness of the method is shown through simulation and real experimentation.